Total Synthesis of Monocyclic Pyrimidinium Betaines With Fatty Alkyl Chains - Malki, Fatiha; Touati, Abdelkader; Rahal, Said; Moulay, Saad (Asian Journal of Chemistry, 2010)
Seven betaines were prepared by condensation of N,N'-diphenylamidines with malonic acid derivatives. The amidines were made via a multistep synthesis, starting from their corresponding fatty acids. Malonyl chloride and dipentachlorophenyl phenylmalonate, two derivatives of malonic acid, were obtained from malonic acid and benzyl chloride, respectively. Most of the products were characterized by IR, UV, 1H and 13C NMR. Biological assays of the synthesized betaines revealed their good antibacterial and antifungal activities against the Pseudomonas aeruginosa, Bacillus subtilis and Mucor ramannianus and an activity against Candida albicans.